ANALISIS PERBANDINGAN METODE TAM DAN METODE UTAUT 2 DALAM MENGUKUR KESUKSESAN PENERAPAN e-Puskesmas DI PUSKESMAS KABUPATEN GROBOGAN - Ferika Indrasari; Windy Nur Lestari; Agus Sulaeman (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
The application of information technology in the health sector, especially the e-Puskesmas system, is intended to improve the quality of services at the Grobogan Regency Community Health Center. The main objective of the study was to analyze the comparison between two models: the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). The study was conducted at the Grobogan Regency Community Health Center from January to March 2025. The population in this study was pharmaceutical personnel at the Grobogan Regency Community Health Center, and the sample in the study consisted of 90 people. The method in this study was comparative quantitative, with data quality testing using validity tests, reliability tests, and one-way ANOVA tests. The results of the one-way ANOVA test showed no significant difference between the TAM method and the UTAUT 2 method, with a sig value of 0.773 > α (0.05), which means there was no significant difference between the TAM method and the UTAUT 2 method in measuring the success of the implementation of the Puskesmas at the Grobogan Regency Community Health Center. This study canit can be concluded that in this study there is no significant difference between the TAM Method and the UTAUT 2 Method in measuring the success of the implementatione-Puskesmasat the Community Health Centers in Grobogan Regency.